Kefanaan Dunia dalam Al-Qur’an: Analisis Tafsir QS Al-Kahfi [18]: 45 Perspektif al-Qurtubi dalam Membangun Self-awareness dan Mindfulness Masyarakat Modern - Rohma, Dika Purnama Aulia (Canonia Religia, 2025)
Modern society, oriented solely towards worldly achievements, experiences inner emptiness, emotional instability, and a crisis of self-awareness. This is caused by a misunderstanding of the world’s nature. The Qur'an clearly states that the world is only a means and an intermediary to achieve true life, namely the hereafter. This paper examines the concept of the transience of the world in QS al-Kahf [18] 45 through the interpretation of al-Qurṭubī, which describes the world as a metaphor for rainwater that grows plants, then dries up and is destroyed by the wind. Using a descriptive-analytical approach and library research methods, this study explores the linguistic meaning and classical interpretations, linking them to the modern human need to cultivate self-awareness and mindfulness. The study shows that al-Qurṭubī identifies five reasons why the world is likened to water: its changeable, temporary, impermanent nature, its trials, and its capacity to contain both benefits and harm. These findings emphasize the importance of placing the world in proportion, not as the ultimate goal, but as a means to eternal happiness, so that fostering self-awareness and mindfulness in society is reflected in actions such as social awareness, the application of Islamic mindfulness in daily life, ecological awareness, and mental resilience that guide humans to live more consciously, balanced, and oriented towards spiritual meaning, not merely material achievements. The implication is that the Qur'anic concept of the transience of the world can be combined with modern psychological perspectives to enhance mental health, promote self-awareness, and cultivate full presence in daily life.